Psychosocial stress and strategies for managing adversity: measuring population resilience in New South Wales, Australia - Jacobs Jennifer; Agho Kingsley; Bryson-Taylor Donald; Stevens Garry; Barr Margo; Taylor Melanie; Raphael Beverley (BMC, 2010)
Abstract Background Populations around the world are facing an increasing number of adversities such as the global financial crisis, terrorism, conflict, and climate change. The aim of this paper was to investigate self-reported strategies and sources of support used to get through "tough times" in an Australian context and to identify patterns of response in the general population and differences in potentially vulnerable subgroups. Methods Data were collected through a cross-sectional survey of the New South Wales population in Australia. The final sample consisted of 3,995 New South Wales residents aged 16 years and above who responded to the question: "What are the things that get you through tough times?" Results Respondents provided brief comments that were coded into 14 main subject-area categories. The most frequently reported responses were family and self (52%); friends and neighbors (21%); use of positive emotional and philosophical strategies (17%), such as sense of humor, determination, and the belief that things would get better; and religious beliefs (11%). The responses of four population subgroups were compared, based on gender, household income, level of psychological distress, and whether a language other than English was spoken at home. Women reported greater use of friends and neighbors and religious or spiritual beliefs for support, whereas men reported greater use of drinking/smoking and financial supports. Those with lower incomes reported greater reliance on positive emotional and philosophical strategies and on religious or spiritual beliefs. Those with high levels of psychological distress reported greater use of leisure interests and hobbies, drinking/smoking, and less use of positive lifestyle strategies, such as adequate sleep, relaxation, or work/life balance. Those who spoke a language other than English at home were less likely to report relying on self or others (family/friends) or positive emotional and philosophical strategies to get through tough times. Conclusions Understanding strategies and sources of support used by the population to get through adversity is the first step toward identifying the best approaches to build and support strengths and reduce vulnerabilities. It is also possible to reflect on how large-scale threats such as pandemics, disasters, conflict, bereavement, and loss could impact individual and population resilience.